Performance Evaluation of Contemporary Software Development Frameworks in Dynamic Environments - Okouma Nguia; Ali Nguia; Joseph Kamala (The Eastasouth Journal of Information System and Computer Science, 2023)
This study presents a comparative performance evaluation of widely used frameworks, including Waterfall, Agile, DevOps, and DevOps integrated with microservices architecture. The evaluation is based on key performance indicators derived from industry-standard metrics such as deployment frequency, lead time, change failure rate, mean time to recovery (MTTR), response time, throughput, scalability, and resource utilization. The findings, illustrated through two analytical figures, demonstrate that traditional frameworks such as Waterfall exhibit limited adaptability, characterized by low deployment frequency, high lead time, and poor scalability. Agile frameworks improve flexibility and responsiveness through iterative development, yet they show moderate performance in handling dynamic workloads. In contrast, DevOps frameworks significantly enhance performance by integrating continuous integration and continuous delivery practices, resulting in improved deployment speed, reduced failure rates, and faster recovery times. The highest level of performance is observed in the DevOps combined with microservices architecture, which achieves superior results across all evaluated metrics. This is primarily due to the decentralized and modular nature of microservices, which allows independent deployment and efficient fault isolation. Overall, the study highlights the critical role of modern software development frameworks in addressing the challenges of dynamic environments. The results provide valuable insights for organizations in selecting appropriate frameworks to optimize performance and maintain competitiveness in rapidly evolving technological landscapes.